2015
DOI: 10.14689/issn.2148-2624.1.3c3s3m
|View full text |Cite
|
Sign up to set email alerts
|

Üstün Yetenekli Öğrencilerin Beden Eğitimi Dersi ve Beden Eğitimi Öğretmeni Kavramlarına Yönelik Algılarının Çizme Yazma Tekniği ile İncelenmesi

Abstract: Bu araştırmanın amacı, Bilim ve Sanat Merkezine katılan üstün yetenekli öğrencilerin beden eğitimi dersi ve beden eğitimi öğretmeni kavramlarına yönelik görüşlerini tespit etmektir. Araştırmanın çalışma grubunu, 2013-2014 Eğitim öğretim yılı bahar döneminde Kırıkkale ve Trabzon illerinde bulunan Bilim ve Sanat Merkezleri'nde öğrenim gören üstün yetenekli 46 öğrenci oluşturmuştur. Araştırmada nitel araştırma yaklaşımı kullanılmıştır. Veriler çizme-yazma tekniği kullanılarak elde edilmiştir. Katılımcılardan elde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 4 publications
0
5
0
2
Order By: Relevance
“…Before preparing the data collection tool, some studies related to subject (Saban, 2008;Cerit, 2008;Aydın & Ünaldı, 2010;Gömleksiz, Kan, & Öner, 2012;Soysal & Afacan, 2012;Ungar, 2016;Yalcın & Erginer, 2012;Tortop, 2013;Özbas & Aktekin, 2013;Demirtas & Coban, 2014;Özsoy, 2014;Emerson & Mansvelt, 2014;Wan, 2014;Yılmaz & Güven, 2015;Cansever & Aslan, 2016) were researched to figure out what kind of data collection tool individual use on determining the metaphoric perceptions towards any concepts, and it was determined that generally as a data collection tool "specific metaphor" approach including open ended question form was used. It was decided to use the "food metaphor" approach for the purpose of determining the gifted students' perceptions towards the concepts of "physical education course" and "physical education teacher".…”
Section: Data Collectionmentioning
confidence: 99%
“…Before preparing the data collection tool, some studies related to subject (Saban, 2008;Cerit, 2008;Aydın & Ünaldı, 2010;Gömleksiz, Kan, & Öner, 2012;Soysal & Afacan, 2012;Ungar, 2016;Yalcın & Erginer, 2012;Tortop, 2013;Özbas & Aktekin, 2013;Demirtas & Coban, 2014;Özsoy, 2014;Emerson & Mansvelt, 2014;Wan, 2014;Yılmaz & Güven, 2015;Cansever & Aslan, 2016) were researched to figure out what kind of data collection tool individual use on determining the metaphoric perceptions towards any concepts, and it was determined that generally as a data collection tool "specific metaphor" approach including open ended question form was used. It was decided to use the "food metaphor" approach for the purpose of determining the gifted students' perceptions towards the concepts of "physical education course" and "physical education teacher".…”
Section: Data Collectionmentioning
confidence: 99%
“…The main reason behind this interest is neither aesthetic pleasure as in arts nor health, wellness and physical training as in sports, rather to have a good time and fun. In a study conducted by Yılmaz & Güven (2015) [14] on gifted children, it was found that the children frequently depicted football in their drawings as it appears frequently as a product of the popular culture. Besides football, different branches of sports have been addressed in the children's picture books included in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…In order to ensure the reliability of research, data were analyzed by an in-field and an out-of-field expert to determine whether the conceptual categories achieved as a result of data analysis represented the themes obtained, and the codes obtained and the categories represented by the codes were compared (Yılmaz & Güven, 2015). Reliability of data analysis in this way was calculated by using the formula "Consensus / (Consensus + Disagreement) x 100" (Miles & Huberman, 1994).…”
Section: Discussionmentioning
confidence: 99%